Simple and partial correlations between the epithelial tissue content of the thyroid, the body weight, age, and level of milk yield in Ayrshire cows - Kossila, Vappu; Heliander, Kaarina (Agricultural and Food Science, 1969)
The absolute amount of the epithelial tissue in the thyroid (Eg) of cows was significantly and more closely correlated with the body weight corrected for pregnancy and/or degree of fatness than with the live weight. Age had practically no effect on the Eg, this observation being of value in case cows of various ages are to be used as material in studies on the incidence of endemic goitre. Due to a group of goitrous cows in the investigated material, significant negative correlation was obtained between the Eg and the milk yield. The implications of this discovery are discussed.